2013
DOI: 10.1111/nph.12174
|View full text |Cite
|
Sign up to set email alerts
|

Drought predisposes piñon–juniper woodlands to insect attacks and mortality

Abstract: SummaryTo test the hypothesis that drought predisposes trees to insect attacks, we quantified the effects of water availability on insect attacks, tree resistance mechanisms, and mortality of mature piñon pine (Pinus edulis) and one-seed juniper (Juniperus monosperma) using an experimental drought study in New Mexico, USA.The study had four replicated treatments (40 9 40 m plot/replicate): removal of 45% of ambient annual precipitation (H 2 OÀ); irrigation to produce 125% of ambient annual precipitation (H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
245
5
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(261 citation statements)
references
References 70 publications
7
245
5
4
Order By: Relevance
“…While for slightly impaired trees a positive trade-off between primary and secondary metabolism is suggested (Bryant et al 1983;Herms & Mattson 1992;Lorio et al 1995), disposable carbon reserves required for repair and maintenance of life-sustaining mechanisms are increasingly depleted in case of severe stress (Niimets 2010). Such link between advanced physiological stress and limited constitutive defence capability in terms of less resin flow was recently demonstrated in response to drought-manipulation in stands of Pinus edulis (Pinyon pine) and P. abies (Gaylord et al 2013;Netherer et al 2015). Drought stress positively or negatively influences the capacity of conifers to prevent the spreading of microorganisms after invasion via hypersensitive wound reaction, which is characterised by the formation of necrotic areas and impregnation of tissues with resinous and phenolic compounds Novak et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…While for slightly impaired trees a positive trade-off between primary and secondary metabolism is suggested (Bryant et al 1983;Herms & Mattson 1992;Lorio et al 1995), disposable carbon reserves required for repair and maintenance of life-sustaining mechanisms are increasingly depleted in case of severe stress (Niimets 2010). Such link between advanced physiological stress and limited constitutive defence capability in terms of less resin flow was recently demonstrated in response to drought-manipulation in stands of Pinus edulis (Pinyon pine) and P. abies (Gaylord et al 2013;Netherer et al 2015). Drought stress positively or negatively influences the capacity of conifers to prevent the spreading of microorganisms after invasion via hypersensitive wound reaction, which is characterised by the formation of necrotic areas and impregnation of tissues with resinous and phenolic compounds Novak et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Exposure to drought may also make trees more vulnerable to insects (Gaylord et al, 2013) and pathogens (Niinemets, 2010). Drought stress enhanced the development of Diplodia pinea on Italian cypress (Madar et al, 1995), Fusarium compactum on Cupressus sempervirens (Madar et al, 1996) and Sphaeropsis sapinea on Pinus resinosa (Blodgett et al, 1997a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above-mentioned causes, plant mortality can be exacerbated by biotic attacks. Several studies have reported a positive relationship between droughts and insect attacks or other pathogens on trees, and both factors have been related to mortality events (Gaylord et al 2013). …”
Section: Introductionmentioning
confidence: 99%